مطبوعات الفقيه العلامة سعيد بن مبارك الصوري - حمود بن حمد بن جويد الغيلاني (المؤتمر الدولي الخامس بماليزيا: حركة الطباعة العُمانية وأثرها في التواصل الحضاري, 2018)
مطبوعات الفقيه العلامة سعيد بن مبارك الصوري حمود بن حمد بن جويد الغيلاني ملخص: مقدمة الدراسة: أهتم العمانيون بالكتابة والتدوين في مختلف العلوم , وتكاد لا تخلو فترة زمنية من وجود اسهامات ونتاجات ثقافية وعلمية , ومن هولاء الذين أثروا المكتبة العمانية العلامة الفقيه سعيد بن مبارك الصوري العماني, الذي بلغت عدد مخطوطاته نحو عشرين مخطوطا ,طبع عدد منها , ولم يسعفه الزمن ولا الظروف في طباعة البقية من مخطوطاته , نتيجة لظروف سياسية و صحية . هدف الدراسة: تهدف هذه الورقة ألقاء الضوء على كتب العلامة الفقيه المطبوعة , وهي , الدرر المضيئة في شرح الدروس الفقهية, و قول الخلف والاسلاف في منع بيع الأوقاف, و دروس التوحيد, دروس التجويد, دروس الفقه, و كتاب قاعدة المدرسة الصورية الدينية منهجية الدراسة: تتخذ هذه الدراسة المنهج الوصفي التحليلي وتتكون من مقدمة وخاتمة, تركز المقدمة التعريف بالشيخ ومساره العلمي ويتناول المبحث الأول جهوده في الطباعة، ويركز المبحث الثاني مشكلة الدراسة زأهميتها وحدودها , ويتناول المبحث الثالث تعريف بكتبه المطبوعة, أما المحور الرابع طريقة واجراءات البحث والنتائج وتحليلها . مصادر الدراسة: ستعتمد الدراسة على مصادر ومراجع أوليه وثانوية التي أشارتعلى هذا النشاط. كلمات مفتاحية : الصوري , مكة , المدينة , الطباعة , المدرسة الدينية الصورية. The commercial activity of Omanis in the 17th and 18th centuries. Introduction: The Omanis played a major role in the history of navigation and maritime trade in various periods, but it declined at the beginning of the sixteenth century AD as a result of the Portuguese occupation of the region and the presence of the English, French and Dutch. Despite the brutal methods followed by the Europeans, but Omanis continued their activity despite Harassment and abuse, and became more prominent after the liberation of the Yarabah to Oman and the Arabian Gulf and followed the Portuguese in the Indian Ocean. Objective of the study: This paper aims to shed light on the commercial activity of Omanis in the 17th and 18th centuries. The methodology of the study: This study takes the historical analytical descriptive approach. It consists of three sections with an introduction and a conclusion. The introduction focuses on Omani maritime activity before the seventeenth century. The first topic deals with the impact of the European presence on commercial navigation in the west of Indian Ocean. The second deals with commercial navigation of Omanis in the seventeenth and eighteenth, the third deals with models of Omani ships and masters of the sea in the eighteenth century. The conclusion provides an overview of the findings of the study. Study sources: The study will be based on primary and secondary sources and references, which are mentioned above.